Teacher's Duties in the Al-Quran Perspective, Tafsir Surah Al-Baqarah Verse 151 - Nurchamidah; Nur Laela; Baso Syafaruddin; Muhammad Hamsah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Some of the teacher's tasks that every teacher should pay attention to and carry out are: 1. Reading Allah's Verses in the first lesson of all lessons in a day. This requires teachers or educational units to make learning the Koran an opening for all learning activities. This is done in order to open the door to Allah SWT's mercy. and prepare students' souls to receive the next lessons. 2. Purify students, where purification includes cleansing from damaged aqidah, from despicable morals, changing and perfecting their reasoning power through divine knowledge towards decisions that are based on sound reason and mature thinking, legal order and civilisation. 3. Teaching the Bible and wisdom, so a teacher must know the needs of students